2020
DOI: 10.1186/s12962-020-00228-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic linkages among economic development, environmental pollution and human health in Chinese

Abstract: Background Research on the relationships between economic development, energy consumption, environmental pollution, and human health has tended to focus on the relationships between economic growth and air pollution, energy and air pollution, or the impact of air pollution on human health. However, there has been little past research focused on all the above associations. Methods The few studies that have examined the interconnections between the economy, energy consumption, environmental pollution and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the literature (e.g. Li, Lin, and Chiu, 2020) it is noted that one of the main goals of sustainable development is the sustainability of the balance between the dimensions under consideration. Alipouri et al (2020) indicated that sustainable development denotes the balanced status among various dimensions of development that aim to improve conditions of quality of human life, while Li et al pointed out that research on the relationships between economic and environmental development focused only on a few aspects of this development.…”
Section: Study Results and Discussionmentioning
confidence: 99%
“…In the literature (e.g. Li, Lin, and Chiu, 2020) it is noted that one of the main goals of sustainable development is the sustainability of the balance between the dimensions under consideration. Alipouri et al (2020) indicated that sustainable development denotes the balanced status among various dimensions of development that aim to improve conditions of quality of human life, while Li et al pointed out that research on the relationships between economic and environmental development focused only on a few aspects of this development.…”
Section: Study Results and Discussionmentioning
confidence: 99%
“…The empirical research shows that New Taipei City and Taipei City have the best performances in terms of MetaFrontier Efficiency and the technology gap ratio. Li et al (2020) apply a modified two-stage Undesirable Meta Dynamic Network model to jointly analyze energy consumption, economic growth, air pollution, and health treatment data in 31 Chinese cities. Their results show that high-income cities have higher average efficiencies than uppermiddle income cities.…”
Section: Air Quality Efficiency Evaluation Based On Data Envelopment Analysis Methodsmentioning
confidence: 99%
“…In China, air pollutants including PM 2.5 (particulate matter with a diameter less than 2.5 μm) and PM 10 (particulate matter with a diameter less than 10 μm) and gaseous pollutants including nitrogen dioxide (NO 2 ), sulfur dioxides (SO 2 ), ozone (O 3 ), and carbon monoxide (CO) have been regularly monitored (Liu et al 2021a). Air pollutants, especially particulate matters, have been found to be linked with different disorders including respiratory, neural, and cardiovascular diseases (Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%